Fabrication and Evaluation of Poly(2-hydroxyethyl methacrylate)/Eudragit L-100 Hydrogels with Fusidic Acid to Promote Eczema Treatment - Koyuncu, Rukiye Miray Cinar; Acarali, Nil (AMER CHEMICAL SOC, 2023)
In this study, hydrogelscontaining 2-hydroxyethyl methacrylate(HEMA), Eudragit L-100, and fusidic acid in different compositionswere prepared with the confinement method by using ammonium persulfate(APS) as a chemical initiator and ethylene glycol dimethacrylate (EGDMA)as a cross-linker to determine the most suitable formulation for usein eczema treatment. Fusidic acid (FA)-confined pHEMA/Eudragit L-100 in synthesis of the hydrogel was used with theTaguchi method, and the optimum synthesis conditions were determined.The swelling percentages of the hydrogels were calculated in differentpH environments and distilled water. Also, the cream formulationsdeveloped and contained in chitosan and HEMA-based polymers were synthesized.Viscosity and pH values changed between 30,000 and 100,000 cP andbetween 5 and 6 for different cream formulations with various conditions,respectively. Also, swelling percentages of hydrogels were between20 and 40. Fourier transform infrared spectroscopy (FTIR) and scanningelectron microscopy (SEM) analyses were performed to characterizethe hydrogel structure and the cream formulations. In addition, thestability of the formulations to 28 days and the changes in parameterssuch as appearance, centrifugation, pH, relative density, viscosity,spreading were evaluated, comparatively.
Keywords: FORMULATION; DELIVERY; CREAM; CHITIN; GEL; Chemistry